DMSO supplementation during in vitro maturation of bovine oocytes improves blastocyst rate and quality - Ynsaurralde Rivolta, Amada Eugenia (2020)
The molecule Dimethyl sulfoxide is widely used as drug solvent. However, its antioxidant property was poorly explored. In this study, we evaluated the effect of DMSO supplementation during oocyte in vitro maturation (IVM) on embryo development and quality. Bovine oocytes were matured with different DMSO concentrations (0, 0.1, 0.25, 0.5, 0.75, 1 and 10% v:v) followed by in vitro fertilization. Subsequently, quality indicators such as gene expression of SOX2, OCT4, CDX2, SOD1, oocyte and embryo redox status and DNA damage were evaluated. Polar body extrusion and blastocyst rates increased with 0.5% v:v DMSO. Moreover, first polar body extrusion and blastocyst rates did not increase with 1%, and 10% of DMSO reduced polar body extrusion and did not produce blastocyst. Optimal concentration of DMSO for the use on the maturation was estimated at around 0.45% v:v. Supplementation with 0.5% v:v DMSO has not affected mRNA abundance of genes key in blastocyst, however 0.75% increased gene expression of OCT4 and SOX2. Oocytes matured with 0.5% v:v DMSO and blastocyst from DMSO group showed reduced lipid peroxidation respect control. Total Glutathione concentrations increased in blastocyst stage in DMSO group. DMSO increased the total cell number of blastocysts but not TUNEL positive cells. In conclusion, our results suggest that low DMSO concentrations used during bovine oocytes in vitro maturation increases the maturation, as well as the blastocyst rate and its quality, without demonstrating deleterious effect on embryo cells.